2022
DOI: 10.1002/jhet.4550
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, antimicrobial evaluation, and in‐silico studies of some 4‐thiazolidinone hybrids bearing coumarin and pyridine moieties

Abstract: Antimicrobial resistance is a major threat to mankind. Many frontline medications are ineffective against antimicrobial-resistant strains which are also responsible for the high mortality rate worldwide. The urgency to create new sets of antimicrobial agents is a priority in present circumstances. In continuation to this, we have strategically designed and synthesized some novel hybrids of 4-thiazolidinone bearing coumarin and pyridine cores for the evaluation of antimicrobial efficacy. A three-step multicompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Their MIC values were measured at 0.5 μg/mL, indicating a higher potency compared to the standard drug fluconazole. Additionally, it was observed that compounds 16c and 16d exhibited a moderate inhibitory impact on isolates resistant to fluconazole, as evidenced by their (MIC) values ranging from 1-32 μg/mL [4].…”
Section: 24-triazoles Bearing a 5-benzoyl Benzimidazol-2ylthio Side C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their MIC values were measured at 0.5 μg/mL, indicating a higher potency compared to the standard drug fluconazole. Additionally, it was observed that compounds 16c and 16d exhibited a moderate inhibitory impact on isolates resistant to fluconazole, as evidenced by their (MIC) values ranging from 1-32 μg/mL [4].…”
Section: 24-triazoles Bearing a 5-benzoyl Benzimidazol-2ylthio Side C...mentioning
confidence: 99%
“…Despite the existence of several antifungal medications, the death rate linked to (IFIs) frequently surpasses 50% [2]. Based on estimations, a significant portion of overall mortality, ranging from 20% to 40%, can be linked to nosocomial infections resulting from Candida albicans [3,4] which is the predominant fungal pathogen within the Candida genus and is responsible for the majority of invasive infections [5].…”
Section: Introductionmentioning
confidence: 99%